Equilibrium molecular dynamics modeling of diffussion and adsorption of fluids in armchair single walled carbon-nanotube - Kio, Michael; Asproulis, Nikolaos; Könözsy, László Z.; Drikakis, Dimitris (International Astronautical Federation (IAF), 2014)
The aim of this paper is to study adsorption and diffusion of gases and liquids especially Argon and Carbon-dioxide in single walled carbonnanotube at room temeperature using equilibrium molecular dynamic simulation. The simulation domain is developed by the large atomic/molecular massively parallel simulator (LAMMPS). The domain consists of a simulation box of volume 100 x 100 x 100 A having periodic boundary conditions at the x. y and z direction.The adsorption and diffusion of different chiral- ity of carbonnanotubes are reported. The Molecular Dynamics Simulation (MD) result shows that single walled carbonnanotube have affinity to attract carbon dioxide to itself than argon, with argon acting as a catalyst for adsorption of more C02 confirming a high adsorption at higher loading. The highest adsorption and diffussion inside the Single-walled carbon-naotube (SWCNT) was determined at certain loading and temperature. The SWCNT is as-sumed to be rigid due to the fact that, flexibility is insignificant and can increase computational time. This study will bring about a better understanding of storage and filtering of gases in SWCNTs and so leading its usefullness in applications such as gasification for jet engines, Co2 removal in the international space station, desalination for water systems, air purification, longer space batteries and enhanced oil recovery.